2011
DOI: 10.1017/s1041610210002073
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Revised Memory and Behavior Problems Checklist Scale (SpRMBPC): trans-cultural adaptation and validation of the RMBPC questionnaire

Abstract: SpRMBPC is a validated tool for assessing the dementia stage and the psychiatric morbidity of patients and caregivers. The Frequency Disruption and Memory subscales assess specifically patient's disruptive symptoms and dementia stages. These tools can be applied to analyze the burden of the patient's disease and the caregiver's distress in Spanish-speaking populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…While the results suggest that the model 2 showed a marginally acceptable fit to the data, a reduced model with fewer items (from 24 to 17, model 3) shows a better fit, maintaining the original structure of three factors (memory, depressive, and disruptive behaviors) for both the frequency and reaction scales. Therefore, the results of this study support the original structure of the RMBPC (Teri et al ., 1992), and this is consistent with the results of previous studies (González-Salvia et al ., 2011; Roth et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the results suggest that the model 2 showed a marginally acceptable fit to the data, a reduced model with fewer items (from 24 to 17, model 3) shows a better fit, maintaining the original structure of three factors (memory, depressive, and disruptive behaviors) for both the frequency and reaction scales. Therefore, the results of this study support the original structure of the RMBPC (Teri et al ., 1992), and this is consistent with the results of previous studies (González-Salvia et al ., 2011; Roth et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Losada et al (2008) found that the Spanish version of the RMBPC showed adequate reliability indexes for the frequency and reaction scales, but they did not analyze the factor structure of the scale or the reliability and validity of the specific subscales. Although this questionnaire was adapted for poorly-educated caregivers from Argentina, it is unclear to what extent it is understandable by other Spanishspeaking caregivers, and specifically from Spain, and this has been suggested as a limitation of the study (González-Salvia et al, 2011). Both studies indicated that the reliability and validity of the questionnaire was acceptable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has 24 items with Likert‐type response ranging between 0 and 4 for frequency of and stress associated with the behavior (e.g., “Doing things that embarrass you”). Good test–retest reliability in Spanish dementia caregivers has been reported, also significant associations with other measures of behavioral and psychological symptoms of dementia (Salvia et al., 2011). The internal consistency indexes (Cronbach’s alpha) in this study were .78 for the frequency and .87 for the reaction subscale.…”
Section: Methodsmentioning
confidence: 97%